The Influence of Environment in the Alteration of the Stained-Glass Windows in Portuguese Monuments - Palomar, Teresa (2021)
This work presents the results of the exposure of soda-lime, potash-lime and mixed-alkali silicate glasses during ten and twenty months in different Portuguese monuments with historical stained-glass windows to characterize the influence of local environmental conditions. The glass samples were exposed in the Monastery of Batalha (Batalha), the Monastery of Jeronimos (Lisbon), and the Cathedral of evora (evora). A set of analytical techniques to assess the physicochemical effects were used, including optical microscopy and Fourier transform infrared spectroscopy. All the samples presented crystalline deposits on their surface; however, their quantity and nature depended on the atmospheric conditions during the days before the collection. Potash-lime silicate glass was the most altered glass in comparison with soda-lime and mixed-alkali silicate glasses. The samples from the Cathedral of evora showed a high content of dust and salts on their surface but without severe chemical pathologies; however, those samples exposed in the Monastery of Jeronimos and the Monastery of Batalha presented alteration layers due to a high humidity environment.